Occupational Exposure to Potentially Infectious Biological Material Among Physicians, Dentists, and Nurses at a University - Leonardo Amaral Reis; Ehideé Isabel Gómez La-Rotta; Priscilla Barbosa Diniz; Francisco Hideo Aoki; Jacks Jorge (Elsevier, 2019)
Objective: The objective of this study was to evaluate the prevalence and incidence of accidents with biological material, the level of knowledge, and compliance to standard precautions (SPs) among dentists, physicians, nurses, and dental and medical students. Methods: A closed cohort study with a prospective and retrospective component was conducted between August 2014 and September 2015. The participants were contacted in two moments during the follow-up period, during which a structured questionnaire divided into six sections was used; the interviews were conducted during the follow-up period (Month 6) and at the end of the observation period (Month 12). Results: The global prevalence of accidents in the previous 12 months was 10.2%, with a difference between professionals and students (13.0% vs. 5.1%, respectively; p < 0.003). The incidence rate was 6.49 per 100 person/year, with difference between the groups (6.09 per 100 person/year in professionals and 7.26 per 100 person/year in students), type of specialization (hazard ratio, 3.27), and hours worked per week (hazard ratio, 2.27). The mean of compliance to SP was 31.99 (±3.85) points, with a median of 33 (30, 35) points against the expected 27.75 points. Adherence to SP was associated with the accident report (p < 0.020). Conclusion: We conclude that the proportion/incidence rate of accidents with biological material was high in relation to that in the literature, being higher in professionals and especially among physicians. The levels of knowledge and adherence to SP were good, with the best found in dentists and dental students. Keywords: Accidents at work, Compliance to standard precautions, Incidence, Needle stick injuries, Prevalence